Representaciones sociales de un grupo de adolescentes de grado 10º frente al rendimiento académico en estudio virtual y post pandemia (2023)
Although online education provided a temporary solution to ensure educational continuity in emergency situations during COVID-19, this research aimed to analyze students' social representations of virtual and later in-person education. The findings reveal that students' social representations of distance education are characterized by a lack of motivation, a feeling of not having learned anything, a lack of support from teachers in the virtual environment, and a negative view of online classes.